Rapid amplification of cDNA end of metallothion in gene during necrosis of plant cells from morinda citrifolia - Lee, Jong Jen (Universiti Malaysia Sarawak (UNIMAS), 2008)
The objective is to determine the presence of cysteine protease gene in the cDNA fragment being synthesized and determining the efficiency of the 3’RACE PCR approach for amplification of cDNA end. Morinda citrifolia is from the family Rubiaceae. It is the plant with great medicinal values. The property of this plant has not been characterized thoroughly in previous time. Cysteine protease play important role in plant growth and development in addition to protein degradation process in plant. Better understanding of the biochemical properties will be attained through the study of cysteine protease gene. The amino acids sequences of this enzyme govern the functional characteristic of this enzyme. Therefore, the termini of the cDNA encoding cysteine protease are amplified through Rapid Amplification of cDNA ends (RACE). This experiment was to amplify the 3’ terminal of the cDNA nucleotide sequence. The RNA extraction was the preliminary step of the reverse transcription reaction to get the coding RNA fragment. First strand cDNA constructed was used for further step of 3’ RACE by using gene specific primer and primers that enabled amplification 3’terminal nucleotides. The PCR products were gel extracted and sent for sequencing. Purified PCR products were cloned for further characterization and analysis of the isolated gene. The gene isolated was found to be similar to metallothionein-like gene and drought stress-induced gene when analysed through Blast.